The Mammalian Olfactory Bulb Contributes to the Adaptation of Odor Responses: A Second Perceptual Computation Carried Out by the Bulb - Storace, Douglas A.; Cohen, Lawrence B. (SOC NEUROSCIENCE, 2021)
While humans and other mammals exhibit adaptation to odorants, the neural mechanisms and brain locations involved in this process are incompletely understood. One possibility is that it primarily occurs as a result of the interactions between odorants and odorant receptors on the olfactory sensory neurons in the olfactory epithelium. In this scenario, adaptation would arise as a peripheral phenomenon transmitted to the brain. An alternative possibility is that adaptation occurs because of processing in the brain. We made an initial test of these possibilities using a two-color imaging strategy to simultaneously measure the activity of the olfactory receptor nerve terminals (input to the bulb) and mitral/tufted cell apical dendrites (output from the bulb) in anesthetized and awake mice. Repeated odor stimulation at the same concentration resulted in a decline in the bulb output, while the input remained relatively stable. Thus, the mammalian olfactory bulb appears to participate in generating the perception of olfactory adaptation under this stimulus condition. Similar experiments conducted previously showed that the bulb may also participate in the perception of concentration invariance of odorant recognition (Storace and Cohen, 2017); thus, the bulb is simultaneously carrying out more than one computation, as is true of other mammalian brain regions and perhaps is the case for all animals with sophisticated nervous systems. However, in contrast with other sensory systems (Van Essen et al., 1992), the very first processing stage in the olfactory system has an output that may directly represent perceptions.